Taste and sight a corpus analysis of English adjective-noun constructions - Sandford, Jodi L. (2019)
Embodiment is central to the Cognitive Linguistics enterprise. The grounding of language in body experience is one of the major tenets of linguistic description at various levels of analysis. We receive the infor-mation of the world around us through the bodily sensations; i.e. we per-ceive, then process and conceptualize it. Research into the sensory do-mains has continued to elicit further examination of how we use meta-phoric and metonymic cross-modal conceptualization in language. Inves-tigation has been carried out both on the single sense domains of touch, taste, smell, hearing, and sight, but also on cross-modality or synesthetic phenomena. Linguistic transfer between various senses seems to respect a hierarchy from the lower (touch, taste, smell) to the higher senses (hear-ing and sight), even though some variation of this hierarchy has been noted. The present study is the first part of a two-fold analysis of cross-modal linguistic mappings that exist between the senses of taste and sight. The objective is to verify what collocations occur between the two do-mains: do they respect the hierarchy, and how frequent, or how strong are they? Corpus analysis of the construction of the adjective + noun type are in keeping with existing literature: the sensory domain that func-tions as source is understood as an adjective modifying another sensory domain, which is found in the form of a noun. This research concentrates on cross-modal pairs found through a corpus-based analysis of taste ad-jectives in the description of vision nouns, e.g. delicious colors. Linguis-tic data were retrieved from corpora that allow for comparison of the ac-tual usage and definition of these constructions. These include the Cor-pus of Contemporary American English (COCA), and the Mapping Meta-phor with the Historical Thesaurus of English. The experimental method-ology is in keeping with the usage-based approach of Cognitive Linguis-tics, considering frequency and relevance.
Otjelovljenost je središnji pojam u okviru kognitivnolingvističke paradigme. Utemeljenost jezika u tjelesnom iskustvu jedna je od glavnih postavki u opisu jezika na različitim razinama. Putem tjelesnih osjeta primamo, a potom obrađujemo i konceptualiziramo, informacije o svijetu. Istraživanja osjetilnih domena kontinuirano potiču daljnje studije o tome kako se koristimo metaforičkom i metonimijskom višeosjetilnom konceptualizacijom u jeziku. Istražuju se pojedinačne osjetilne domene dodira, okusa, mirisa, sluha i vida, ali i višeosjetilnost, odnosno sinestetske pojave. Jezični prijenos između različitih osjeta, čini se, ravna se prema hijerarhiji koja ide od nižih (dodir, okus, miris) prema višim osjetima (sluh i vid), iako su zapažena neka odstupanja. Ova je studija prvi dio dvodijelne analize jezičnih preslikavanja koja uključuju modalitete okusa i vida. Cilj je utvrditi koje se kolokacije uspostavljaju među dvama domenama, ravnaju li se one prema spomenutoj hijerahiji, koliko su česte te koliko su jake. Rezultati analize korpusa konstrukcija tipa pridjev + imenica podudaraju se s nalazima iz literature: osjetilna domena koja funkcionira kao izvorna domena interpretira se kao pridjev koji modificira drugu osjetilnu domenu koja se leksikalizira kao imenica. Ovo se istraživanje usredotočuje na parove pronađene korpusnom analizom pridjeva koji označavaju okus kao modifikatora imenica koje označavaju vidne podražaje, npr. delicious colours (‘ukusne boje’). Jezični podatci crpljeni su iz korpusa koji omogućuju usporedbu aktualne porabe i definiciju tih konstrukcija (Corpus of Contemporary American English (COCA) te Mapping Metaphor with the Historical Thesaurus of English). Eksperimentalna metodologija, tj. uočavanje čestotnosti i relevantnosti, u skladu je s uporabnim modelom kognitivne lingvistike.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija: str. 250-253.
Summary ; Sažetak.
Keywords: Engleski jezik -- Jezične konstrukcije -- Višeosjetilnost -- Korpusna lingvistika -- Kolokacije